Persuasive techniques in out-of-home advertising: A comparative study - Duong Quang Trung; Tran T.M. Thu; Nguyen L.M. Hien (International Journal of Business and Social Science Research, 2025)
This study is conducted with the aim to identify and examine the persuasive techniques employed in billboard and banner advertising within the Vietnamese context, and to further explore their linguistic realizations and emergent persuasive features. It seeks to discover the correlations among persuasive techniques, highlight the similarities and differences in their application between billboards and banners, and propose implications for enhancing marketing and advertising strategies. Employing descriptive, quantitative, and qualitative methods, and drawing on the theoretical frameworks developed by Shabo (2010, 2013), the research analyzes a dataset of 488 OOH advertisements, comprising 244 billboards and 244 banners, collected from Da Nang City and Quang Nam Province. The findings reveal the presence of twelve persuasive techniques, alongside the identification of specific linguistic realization patterns within each technique. Significant correlations among techniques are observed, and both similarities and differences in their deployment across billboards and banners are highlighted. Based on these findings, a proposed model is formulated, emphasizing the synergistic role of emotional, logical, and credibility-based appeals in enhancing persuasive effectiveness in OOH advertising. The study provides practical implications for advertisers and contributes to the academic understanding of persuasive communication strategies in the contemporary Vietnamese advertising landscape.